Irisin and Incretin Hormones: Similarities, Differences, and Implications in Type 2 Diabetes and Obesity - Nicola Marrano; Giuseppina Biondi; Anna Borrelli; Angelo Cignarelli; Sebastio Perrini; Luigi Laviola; Francesco Giorgino; Annalisa Natalicchio (Biomolecules, 2021)
Incretins are gut hormones that potentiate glucose-stimulated insulin secretion (GSIS) after meals. Glucagon-like peptide-1 (GLP-1) is the most investigated incretin hormone, synthesized mainly by L cells in the lower gut tract. GLP-1 promotes β-cell function and survival and exerts beneficial effects in different organs and tissues. Irisin, a myokine released in response to a high-fat diet and exercise, enhances GSIS. Similar to GLP-1, irisin augments insulin biosynthesis and promotes accrual of β-cell functional mass. In addition, irisin and GLP-1 share comparable pleiotropic effects and activate similar intracellular pathways. The insulinotropic and extra-pancreatic effects of GLP-1 are reduced in type 2 diabetes (T2D) patients but preserved at pharmacological doses. GLP-1 receptor agonists (GLP-1RAs) are therefore among the most widely used antidiabetes drugs, also considered for their cardiovascular benefits and ability to promote weight loss. Irisin levels are lower in T2D patients, and in diabetic and/or obese animal models irisin administration improves glycemic control and promotes weight loss. Interestingly, recent evidence suggests that both GLP-1 and irisin are also synthesized within the pancreatic islets, in α- and β-cells, respectively. This review aims to describe the similarities between GLP-1 and irisin and to propose a new potential axis–involving the gut, muscle, and endocrine pancreas that controls energy homeostasis.